Accuracy of Dongjui analyzer for reducing the number of unnecessary urine cultures in an outpatient setting - Ozturk, Murat; Üstündağ, Yasemin; Satır, Atilla; Huysal, Kağan (The European Research Journal, 2022)
Objectives: The purpose of this study was to evaluate the diagnostic performance of the Dongjui DJ-8602 urinary analyzer for reducing the number of unnecessary urine cultures in patients with suspected urinary tract infection (UTI). Methods: This study was designed as a retrospective study performed in patients with suspected UTI from August 1, 2018 to December 1, 2018. Clinical data, C reactive protein, blood hematologic counts were evaluated. Using positive culture results as the gold standard, the cut-off values by the receiver operating characteristic curve technique, sensitivity, and specificity were calculated. Results: The median values of urine leukocyte levels were 31 cells/high power field (HPF) in the culture-positive group and 5 leukocytes/HPF in the culture-negative group, respectively. The area under the curve for leukocyte and bacteria count were 0.753 (95% Cl, 0.642 to 0.862) and 0.581 (95% Cl, 0.438 to 0.725), respectively. A leukocyte count ≥ 2 cells/HPF, resulting the best sensitivity of 96.3% (95% Cl: 81.03% to 99.48%) and a negative predictive value (NPV) of 96.4% (95% Cl: 79.35% to 99.48%). Conclusions: The use of the Dongjui DJ-8602 urinary sediment and chemistry analyzer did not accurately predict the outcome of urine cultures with an unsatisfactory sensitivity and NPVs of bacteria counts.